The myth of racial color blindness: manifestations, dynamics, and impact - Neville, Helen A.; Gallardo, Miguel E.; Sue, Derald Wing (American Psychological Association, 2016)
"Does the election of the first Black president mean that the United States is a 'postracial' society? In this volume, scholars in psychology, education, sociology, and related fields dissect the concept of color-blind racial ideology (CBRI), the widely-held belief that skin color does not affect interpersonal interactions, and that interpersonal and institutional racism therefore no longer exists in America. Contributors survey the theoretical and empirical literature on racial color-blindness; discuss novel ways of assessing and measuring color-blind racial beliefs; examine related characteristics such as lack of empathy and internalized racism; and assess the impact of CBRI across contexts such as education, the workplace, and health care settings"--Provided by publisher